INVESTIGATION OF STUDENT QUANTITATIVE REASONING IN GENERALIZING (CASE STUDY ON FEMALE JUNIOR HIGH SCHOOL STUDENTS) - Nasrun Nasrun; Muhammad Muzaini; Rahmat Kamaruddin (STKIP Andi Matappa, 2023)
Quantitative reasoning holds a significant place in the realm of mathematical education. A primary objective shared by many mathematics educators worldwide is to facilitate the connection between students' mental faculties and their capacity to address real-life problems through mathematical means. A fundamental aspect of this endeavor involves nurturing students' comprehension of quantity, particularly in relation to the characteristics of objects. The central aim is to empower students to harness their quantitative reasoning capabilities. In the context of this study, quantitative reasoning denotes the cognitive process employed by individuals when they identify, interconnect, and formulate novel quantities. Algebra, as a discipline, is now widely recognized as one that investigates the structures, relationships, and quantities within mathematics. To enhance students' grasp of algebra and their ability to generalize, a specific instructional approach is employed. The study targets female students enrolled in a Junior High School in Makassar and seeks to scrutinize their quantitative reasoning proficiency in the context of generalization while considering potential gender disparities. To attain this objective, a qualitative methodology is adopted, providing insights into students' quantitative reasoning abilities as reflected in their actions when completing assigned tasks. Ultimately, the study's findings will provide a comprehensive portrayal of how students engage in quantitative reasoning during the process of generalization, which encompasses stages such as connecting quantities, identifying quantities, and formulating new quantities.